2006
DOI: 10.1213/01.ane.0000242534.84131.c6
|View full text |Cite
|
Sign up to set email alerts
|

The Posterior Approach to the Sciatic Nerve in the Popliteal Fossa: A Comparison of Single- Versus Double-Injection Technique

Abstract: We compared single-injection and double-injection of the sciatic nerve with nerve stimulation in the posterior popliteal approach using mepivacaine 1% in a prospective, randomized and single-blind study to evaluate effectiveness, delay of onset, and complications in patients undergoing foot and ankle surgery. In the single-injection group (Group S, n = 30), 25 mL of mepivacaine 1% was administered after eliciting foot inversion or plantar flexion. In the double-injection group (Group D, n = 30), 12.5 mL of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…No intergroup differences were found in performance times, number of attempts, and success rates (71%–82%). Another RCT (n=60), comparing single-injection and double-injection techniques, reported similar success rates (77%–87%), sensory onset times as well as total anesthesia-related times 187. However, a decreased performance time (4.6±2.8 vs 5.9±3.1 min; p=0.03) and incidence of paresthesia (17% vs 40%; p=0.04) were noted with a single-injection technique.…”
Section: Nerve Blocks Of the Sacral Plexusmentioning
confidence: 90%
“…No intergroup differences were found in performance times, number of attempts, and success rates (71%–82%). Another RCT (n=60), comparing single-injection and double-injection techniques, reported similar success rates (77%–87%), sensory onset times as well as total anesthesia-related times 187. However, a decreased performance time (4.6±2.8 vs 5.9±3.1 min; p=0.03) and incidence of paresthesia (17% vs 40%; p=0.04) were noted with a single-injection technique.…”
Section: Nerve Blocks Of the Sacral Plexusmentioning
confidence: 90%
“…[3][4][5][6][7] However, a double-stimulation technique is not synonymous to separate tibial and common peroneal nerve injections, especially considering that most of these studies used an injection site at or above the expected level of bifurcation of the sciatic nerve. 8 Therefore, given the variability in the point of bifurcation and the blind nature of a stimulating technique, these studies do not definitively determine whether a prebifurcation sciatic block is associated with a different onset time than individual tibial and common peroneal nerve blocks.…”
Section: Discussionmentioning
confidence: 99%
“…36,49,58 In contrast, three other RCTs (pertaining to the subgluteal, posterior and lateral popliteal approaches) failed to detect any such difference. 52,56,59 Although a review of the optimal LA dose required for sciatic nerve blockade exceeds the scope of this paper, it is interesting to note that the studies that found an improved success rate with two injections used a total dose of 20 mL of LA. In contrast, those that did not employed a larger volume (25-30 mL).…”
Section: Discussionmentioning
confidence: 99%
“…However, patients receiving a single injection reported fewer paresthesiae (17 vs 40% of patients; P = 0.04). 56 Although observational studies have suggested that the optimal evoked motor response for posterior popliteal sciatic blockade is inversion, this finding requires further validation with RCTs. 57 Two RCTs have compared single and double-injection techniques for the lateral popliteal approach with conflicting results.…”
Section: Techniquesmentioning
confidence: 99%